Inovasi Pelayanan Administrasi Kependudukan Berbasis Whatsapp di Era Pandemi Covid-19 Di Kelurahan Sempaja Barat Kecamatan Samarinda Utara Kota Samarinda - Sifriya Zullhiza; Iman Surya; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The results of the study show that the innovation of whatsapp-based population administration services organized by the Sempaja Barat Village Office, North Samarinda District, Samarinda City is based on the established research sub-focus, namely Relative Advantage, Compatibility, Complexity, Triability, Observability, the implementation has been carried out well even though it is not optimal. This can be seen from the findings in research, in which there are several research sub-focuses that have been running according to public service standards, including based on the relative advantages of WhatsApp services, the community feels helped and facilitates service, for the suitability of WhatsApp services in accordance with applicable service standards. , for the complexity of the whatsapp service there are still many who do not understand related to the use of whatsapp and prefer to go directly to the field, the whatsapp service is not trialled, the whatsapp service is known by the public through outreach.